Partial purification and characterization of lysine-ketoglutarate reductase in normal and opaque-2 maize endosperms - Brochetto-Braga, Marcia R. [UNESP]; Leite, Adilson; Arruda, Paulo (My University, 1992)
Lysine-ketoglutaratc reductase catalyzes the first step of lysine catabolism in maize (Zea mays L.) endosperm. The enzyme condenses L-lysine and α-ketoglutarate into saccharopine using NADPH as cofactor. It is endosperm-specific and has a temporal pattern of activity, increasing with the onset of kernel development, reaching a peak 20 to 25 days after pollination, and thereafter decreasing as the kernel approaches maturity. The enzyme was extracted from the developing maize endosperm and partially purified by ammonium-sulfate precipitation, anion-exchange chromatography on DEAE-cellulose, and affinity chromatography on Blue-Sepharose CL-6B. The preparation obtained from affinity chromatography was enriched 275-fold and had a specific activity of 411 nanomoles per minute per milligram protein. The native and denaturated enzyme is a 140 kilodalton protein as determined by polyacrylamide gel electrophoresis. The enzyme showed specificity for its substrates and was not inhibited by either aminoethyl-cysteine or glutamate. Steady-state product-inhibition studies revealed that saccharopine was a noncompetitive inhibitor with respect to α-ketoglutarate and a competitive inhibitor with respect to lysine. This is suggestive of a rapid equilibriumordered binding mechanism with a binding order of lysine, α-ketoglutarate, NADPH. The enzyme activity was investigated in two maize inbred lines with homozygous normal and opaque-2 endosperms. The pattern of lysine-ketoglutarate reductase activity is coordinated with the rate of zein accumulation during endosperm development. A coordinated regulation of enzyme activity and zein accumulation was observed in the opaque-2 endosperm as the activity and zein levels were two to three times lower than in the normal endosperm. Enzyme extracted from L1038 normal and opaque-2 20 days after pollination was partially purified by DEAE-cellulose chromatography. Both genotypes showed a similar elution pattern with a single activity peak eluted at approximately 0.2 molar KCL. The molecular weight and physical properties of the normal and opaque-2 enzymes were essentially the same. We suggest that the Opaque-2 gene, which is a transactivator of the 22 kilodalton zein genes, may be involved in the regulation of the lysine-ketoglutarate reductase gene in maize endosperm. In addition, the decreased reductase activity caused by the opaque-2 mutation may explain, at least in part, the elevated concentration of lysine found in the opaque-2 endosperm.